PETA KEPRIBADIAN KONSELOR DALAM PROSES BIMBINGAN DAN KONSELING: SEBUAH TINJAUAN KEPUSTAKAAN [COUNSELOR PERSONALITY MAP IN GUIDANCE AND COUNSELING PROCESS: A LITERATURE REVIEW] - Abrori, Hosnul; As’ari, Jamaludin; Isnaini, Subi Nur (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2023)
The study of guidance and counseling at this time is very much discussed. The counseling process is the provision of assistance to clients who experience problems. This paper tries to examine how the personality of the counselor must be possessed when the counseling process is carried out. This study used the literature review method, where data mining was obtained from searching journal articles and other related sources. This research produced the personality counselors must have, namely: (1) have faith and piety to God, (2) practice God's teachings, (3) have empathy and be able to motivate, (4) uphold human values, (5) appreciate, (6) a sincere heart to help, (7) consistent and responsible, and (8) have intelligence, skills, and a strong personality. This personality functions during pre-counseling, during counseling, and post-counseling.